The Interactive Study of Qiang Salang Dance Culture in Western Sichuan of China - Xinxin, Lan; Maneewattana , Chutima; Qianqiu , Jin (Journal of Roi Kaensarn Academi, 2024)
The objectives of this research were 1) Analyze the cultural interaction of Salang dance2) Analyze the interactive motivation of Salang dance culture 3)Analyze the interactive characteristics of Salang dance culture the sample wasIt is mainly concentrated in the Qiang culture area in western Sichuan, China, and the Qiang nationality is mainly selected as Wenchuan, Li County and MAO County of Aba Tibetan and Qiang Autonomous Prefecture.The research instrument for the data collection were Observation sheet, interview sheetThe statistics for data analysisInteractive factors of Qiang danceThe research results were found as follows; 1)The interaction of the Qiang Salang dance shows both intra-ethnic interaction and extra-ethnic interaction.2)The interactive reasons of Qiang Salang dance include historical factors, four geographical factors and kinship factors.3)The interactive characteristics of the Qiang Salang dance are cultural immersion and cultural interweaving, intra-ethnic interaction and inter-ethnic coexistence.Suggestion:Culturally, learn from each other, learn from each other, develop together and make progress together